Pitavastatin protects against neomycin-induced ototoxicity through inhibition of endoplasmic reticulum stress - Wu, Yunhao; Meng, Wei; Guan, Ming; Zhao, Xiaolong; Zhang, Chen; Fang, Qiaojun; Zhang, Yuhua; Sun, Zihui; Cai, Mingjing; Huang, Dongdong; Yang, Xuechun; Yu, Yafeng; et al. (Frontiers in Molecular Neuroscience, 2022)
Irreversible injury to inner ear hair cells induced by aminoglycoside antibiotics contributes to the formation of sensorineural hearing loss. Pitavastatin (PTV), a 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor, has been reported to exert neuroprotective effects. However, its role in aminoglycoside-induced hearing loss remains unknow. The objectives of the present study were to investigate the beneficial effects as well as the mechanism of action of PTV against neomycin-induced ototoxicity. We found that PTV remarkably reduced hair cell loss in mouse cochlear explants and promoted auditory HEI-OC1 cells survival after neomycin stimulation. We also observed that the auditory brainstem response threshold that was increased by neomycin was significantly reduced by pre-treatment with PTV in mice. Furthermore, neomycin-induced endoplasmic reticulum stress in hair cells was attenuated by PTV treatment through inhibition of PERK/eIF2α/ATF4 signaling. Additionally, we found that PTV suppressed the RhoA/ROCK/JNK signal pathway which was activated by neomycin stimulation in HEI-OC1 cells. Collectively, our results showed that PTV might serve as a promising therapeutic agent against aminoglycoside-induced ototoxicity.